2021
DOI: 10.1101/2021.05.13.444053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Microbeads Stacking in Deformable Nano-Sieve for Efficient Plasma Separation and Blood Cell Retrieval

Abstract: Efficient separation of blood cells and plasma is key for numerous molecular diagnosis and therapeutics applications. Despite various microfluidics-based separation strategies have been developed, a simple, reliable, and multiplexing separation device that can process a large volume of blood is still missing. Here we show a microbead packed deformable microfluidic system that can efficiently separate highly purified plasma from whole blood as well as retrieve blocked blood cells from the device. Combining micr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Polydimethylsiloxane (PDMS) is one of the most popular building materials for deformable microfluidics with the advantages such as high deformability, biocompatibility, and stability 14 . We recently showed that the mechanical properties of the PDMS-based deformable microfluidics enable controlled microparticle capture and release 15 . However, the past studies focused on the fluid-structure interaction in steady flows 1620 .…”
Section: Introductionmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) is one of the most popular building materials for deformable microfluidics with the advantages such as high deformability, biocompatibility, and stability 14 . We recently showed that the mechanical properties of the PDMS-based deformable microfluidics enable controlled microparticle capture and release 15 . However, the past studies focused on the fluid-structure interaction in steady flows 1620 .…”
Section: Introductionmentioning
confidence: 99%